1997
DOI: 10.1021/la960833w
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Kinematics of Polystyrene Bead Suspensions

Abstract: A study of the evaporation of polystyrene sphere−H2O suspensions placed on nonwetting surfaces was conducted using a video camera and computer-imaging interface. The height, diameter, contact angle, and mass were measured as functions of time for a range of sessile drop sizes, polystyrene sphere diameters, and initial suspension concentrations. For initial concentrations of polystyrene spheres greater than approximately 8%, the drop diameter changed by less than 5%, and universal trends, independent of the sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 11 publications
2
59
1
Order By: Relevance
“…Although the formation mechanism of organic crystal rings studied in this report might be different from previous reports involving nanoparticles, [16,17] contact-line pinning and evaporation of solvent are two important factors in ring formation, as illustrated in Figure 4. When we dropped the THF solution of HMTP and HPMMATP onto the silicon wafer, the liquid wet the substrate to form a uniform liquid film.…”
Section: Resultscontrasting
confidence: 82%
“…Although the formation mechanism of organic crystal rings studied in this report might be different from previous reports involving nanoparticles, [16,17] contact-line pinning and evaporation of solvent are two important factors in ring formation, as illustrated in Figure 4. When we dropped the THF solution of HMTP and HPMMATP onto the silicon wafer, the liquid wet the substrate to form a uniform liquid film.…”
Section: Resultscontrasting
confidence: 82%
“…Typically, instead of a uniform deposition, the solutes are preferentially deposited to the edges of the droplet (Conway et al 1997;Deegan et al 1997), resulting in a ring-like deposition pattern upon drying of the droplet. The basic mechanism of ring-like deposition pattern formation is related to a two stage drying process (Picknett and Bexon 1977;Deegan et al 2000;Dhavaleswarapu et al 2010), where initially, the radius of the droplet does not shrink during evaporation, because contact angle hysteresis pins the contact line, and only after the receding contact angle is reached, does the droplet radius start to shrink.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that evaporating droplets containing passive flow markers like polystyrene spheres produce distinct ring stain patterns at the drop periphery [12][13][14][15][16][17] caused by contact line pinning. Numerical [18][19][20] and experimental studies [21][22][23] of small and highly volatile droplets like chloroform evaporating in air at room temperature have also shown that evaporative cooling creates Bénard-Marangoni 11 ͑i.e., surface tension dominated͒ convection patterns above the critical Marangoni number.…”
mentioning
confidence: 99%